Growth mindset and student writing feedback literacy among Chinese learners of Japanese: the mediating role of achievement goals - Chen, Xi; Bai, Xue; Li, Lu; Liu, Xinying (Frontiers in Psychology, 2026)
IntroductionResearch on student writing feedback literacy is increasing, but individual learner factors remain underexamined, and most existing studies focus on English learners rather than Japanese learners. This study explores the relationships between Japanese learners’ growth mindset and student writing feedback literacy, as well as the mediating role of achievement goals.MethodsData were collected through a questionnaire completed by 309 Japanese learners in China. The survey assessed growth mindset, achievement goals, and student writing feedback literacy. Structural equation modeling (SEM) and bootstrapped mediation analysis were used to examine the direct and indirect relationships among the variables.ResultsSEM results revealed that the direct effect of growth mindset on student writing feedback literacy was not significant. Mediation analyses showed that development-approach, development-avoidance, and demonstration-approach goals positively mediated the relationship between growth mindset and student writing feedback literacy, with all indirect effects being statistically significant.DiscussionAchievement goals serve as a key mediating mechanism linking Japanese learners’ growth mindset and student writing feedback literacy. Such practices as development-oriented instructional goals and formative assessment may provide a supportive context for fostering a growth mindset and development-focused achievement goals, thereby supporting the development of student writing feedback literacy.